Collection Creation as Collection Management: Libraries as Publishers and Implications for Collection Development - Gwynn, David; Henry, Tiffany; Craft, Anna R. (Collection management, 2019)
Digital collections, institutional repositories, open educational resources, open access publishing, and new forms of digital scholarship are all ways in which academic libraries are growing their collections from the inside out as well as making this content widely available to other libraries and users. This article will explore national and global trends in library-enabled publishing and content creation, focusing on the kinds of collections being published by libraries, the ways that metadata can bring these collections together for improved access, and the role of consortia in the process.